The Effect of a Continuous Milk Warming System on Weight Gain in Very Low Birth-Weight Infants: A Randomized Controlled Trial. (August 2021) - Bedwell, Susan M.; Buster, Barbara; Sekar, Krishnamurthy
Abstract : Background: Few studies support the practice of warming human milk before feeding. No studies have compared the method of warming milk and its effect on growth, particularly in preterm infants. Purpose: To evaluate growth in preterm infants receiving continuously warmed human milk as compared with infants receiving human milk warmed in a hot water bath before feeding. Methods: Forty-four infants less than 32 weeks' gestation admitted to a regional referral level IV neonatal intensive care unit in south central United States were randomly assigned to either the experimental group (continuous warming: n = 22) or the control group (hot water bath: n =22) for 10 days. All infants were on full human milk feedings (120-130 kcal/kg/d) as part of a standardized feeding protocol. Tolerance and weight gain over the 10-day period were used to evaluate the effectiveness of continuous milk warming. Results: There was a significant difference in weight gain for infants receiving continuously warmed milk compared with infants receiving standard warmed milk (203.73 ± 70.71 vs 271.95 ± 67.40, P = .002). Implications for Practice: The use of continuous milk warming improves weight gain in very low birth-weight infants.